Estresse oxidativo e vesículas extracelulares na doença renal do diabetes - Sara de Castro Oliveira (2024)
Diabetic kidney disease (DKD) is an important cause of morbimortality in the adult population with Type 1 Diabetes Mellitus (T1DM). The development of DKD is complex and multifactorial, being associated with metabolic disarrangements (glucose and lipid control), increase in inflammatory and oxidative stress status, activation of the reninangiotensin-aldosterone cascade and other hemodynamics abnormalities (hypo or hyper glomerular filtration). More recently, the role of microRNAs carried by extracellular vehicles (EVs) or freely circulating in the blood has been suggested as a new possible mechanism of DKD establishment. In this context, new markers have been explored since some patients with DKD evolve with kidney failure despite not present albuminuria. Our study explored the association of abnormalities in extracellular vehicles (EVs) and oxidative stress markers in three distinct groups of clinical outpatients: normal controls, T1DM (without DKD), and DKD. For this study, approved by the Ethics committee, controls and T1DM were recruited at the Diabetes outpatient clinics at IPSEMG and/or at Hospital das Clinicas da UFMG. Overall, 124 participants, 61 normal controls, 42 T1DM (without DKD), and 21 DKD defined according the KDIGO guidelines were included. Clinical (anthropometry data, blood pressure, evaluation of the presence of diabetes micro-and-macrovascular complications) and biochemical data (glucose levels, kidney function evaluation, albumin/creatinine ratio, lipid profile and C reactive protein) were obtained from these groups. The isolation and characterization of EVs from serum were obtained through a series of processes, including the ultracentrifugation and characterization of EVs was identified by specific protein markers by western blot morphology checked by Scanning Electron Microscope (FEI Tecnai 20; LAB6 emission; 200 kV). EVs particle size and concentration were determined by NanoSight NS300 instrument (Malvern Panalytical, UK). Total Oxidant Status (TOS), Total Antioxidant Capacity (TAC), Advanced Oxidation of Protein Products (AOPP), (Ferric Reducing Antioxidant Power), C reactive Protein, Uric Acid, Aloxan levels were determined in the serum or the plasma. The three groups (control+ DM1+ DM1 DKD) were similar regarding age (mean± SD) of 40.3 ± 13.7 years, BMI 25.8 ± 5.1 Kg/m2, and Abdominal Circumference 89.6 ± 12.3 cm. The albumin/creatinine ratio was statistically different among the groups, 10 being its (median [95%CI]) of 4.0 [3.9-5.14] mg/g in Controls, 6.4[5.5-10.0]mg/g in T1DM, and 81.4 [48.5 -1415] mg/g in DKD (p